2000
DOI: 10.1039/a908744c
|View full text |Cite
|
Sign up to set email alerts
|

Role of weak hydrogen bonds in the crystal structures of phenazine, 5,10-dihydrophenazine and their 1:1 and 3:1 molecular complexes

Abstract: Phenazine (1) and 5,10-dihydrophenazine (2) form not only a 1 : 1 complex (3), as expected from NÈHÉ É ÉN hydrogen bond requirements, but surprisingly also a 3 : 1 complex (4). Single crystal X-ray analyses of compound 2 and complexes 3 and 4 have been carried out. While the overall packing in complex 3 is as efficient as in pure 1 and 2, acidic CÈH groups, which contribute actively to the structural assembly in pure 2, are not involved in hydrogen bonding in 3. It is shown that the quest for hydrogen bonding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
27
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 1 publication
2
27
0
Order By: Relevance
“…Additionally it can be involved as a donor in weak C-HÁ Á ÁX interactions and participate in diverse aromatic interactions. Whereas its analogue with an expanded system of condensed rings and higher molecular symmetry, phenazine (PHZ), has been extensively used as a reagent in supramolecular synthesis (Batchelor et al, 2000;Gdaniec et al, 2005;Kutasi et al, 2002;Munakata et al, 1994;Pedireddi et al, 1996;Tomura & Yamashita, 2000;Thalladi, Smolka, Gehrke, Boese & Sustmann, 2000), much less work has been done with QX. have shown that PHZ forms cocrystals with some biphenols where PHZ molecules, arranged into stacks, form a robust host framework with one-dimensional channels filled by the phenolic molecules.…”
Section: Commentmentioning
confidence: 99%
“…Additionally it can be involved as a donor in weak C-HÁ Á ÁX interactions and participate in diverse aromatic interactions. Whereas its analogue with an expanded system of condensed rings and higher molecular symmetry, phenazine (PHZ), has been extensively used as a reagent in supramolecular synthesis (Batchelor et al, 2000;Gdaniec et al, 2005;Kutasi et al, 2002;Munakata et al, 1994;Pedireddi et al, 1996;Tomura & Yamashita, 2000;Thalladi, Smolka, Gehrke, Boese & Sustmann, 2000), much less work has been done with QX. have shown that PHZ forms cocrystals with some biphenols where PHZ molecules, arranged into stacks, form a robust host framework with one-dimensional channels filled by the phenolic molecules.…”
Section: Commentmentioning
confidence: 99%
“…[6] Their importance in the stabilization of conformations and structures of proteins and DNA has also been suggested in recent years. [7] On the other hand, supramolecular polymers, assembled from low molecular weight monomeric units by specific directional secondary interactions, such as hydrogen bonds, p-p interactions, hydrophobic interactions, and metal-ligand bonds, have demonstrated traditional polymeric properties and become an important part of stimuli-responsive dynamic materials.…”
mentioning
confidence: 99%
“…[1c] However, they have played significant roles in various fields of chemistry and biological systems, for example in determining the conformations of molecules, [2] crystal packing, [3] host-guest chemistry, [4] reaction selectivity, [5] and the self-assembly of molecules into organized supramolecular structures. [6] Their importance in the stabilization of conformations and structures of proteins and DNA has also been suggested in recent years. [7] On the other hand, supramolecular polymers, assembled from low molecular weight monomeric units by specific directional secondary interactions, such as hydrogen bonds, p-p interactions, hydrophobic interactions, and metal-ligand bonds, have demonstrated traditional polymeric properties and become an important part of stimuli-responsive dynamic materials.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1] They are weaker than the classical hydrogen bonds between NH/O, NH/N, O/OH, and N/OH groups (3-7 kcal mol À1 ). [6] Their importance in the stabilization of conformations and structures of proteins and DNA has also been suggested in recent years. [6] Their importance in the stabilization of conformations and structures of proteins and DNA has also been suggested in recent years.…”
mentioning
confidence: 99%